Rational and Efficient Preparative Isolation of Natural Products by MPLC-UV-ELSD based on HPLC to MPLC Gradient Transfer - Challal, Soura; Queiroz, Emerson Ferreira; Debrus, Benjamin; Kloeti, Werner; Guillarme, Davy; Gupta, Mahabir Prashad; Wolfender, Jean-Luc (Planta Medica, 2015)
In natural product research, the isolation of biomarkers or bioactive compounds from complex natural extracts represents an essential step for de novo identification and bioactivity assessment. When pure natural products have to be obtained in milligram quantities, the chromatographic steps are generally labourious and time-consuming. In this respect, an efficient method has been developed for the reversed-phase gradient transfer from high-performance liquid chromatography to medium-performance liquid chromatography for the isolation of pure natural products at the level of tens of milligrams from complex crude natural extracts. The proposed method provides a rational way to predict retention behaviour and resolution at the analytical scale prior to medium-performance liquid chromatography, and guarantees similar performances at both analytical and preparative scales. The optimisation of the high-performance liquid chromatography separation and system characterisation allows for the prediction of the gradient at the medium-performance liquid chromatography scale by using identical stationary phase chemistries. The samples were introduced in medium-performance liquid chromatography using a pressure-resistant aluminium dry load cell especially designed for this study to allow high sample loading while maintaining a maximum achievable flow rate for the separation. The method has been validated with a mixture of eight natural product standards. Ultraviolet and evaporative light scattering detections were used in parallel for a comprehensive monitoring. In addition, post-chromatographic mass spectrometry detection was provided by high-throughput ultrahigh-performance liquid chromatography time-of-flight mass spectrometry analyses of all fractions. The processing of all liquid chromatography-mass spectrometry data in the form of an medium-performance liquid chromatography x ultra high-performance liquid chromatography time-of-flight mass spectrometry matrix enabled an efficient localisation of the compounds of interest in the generated fractions. The methodology was successfully applied for the separation of three different plant extracts that contain many diverse secondary metabolites. The advantages and limitations of this approach and the theoretical chromatographic background that rules such as liquid chromatography gradient transfer are presented from a practical viewpoint.
Keywords: natural products; plant extracts; HPLC-UV-ELSD; MPLC-UV-ELSD; UHPLC-TOF-MS; gradient transfer; isolation